Stocking of Lobster (Panulirus spp.) for Community Empowerment in Gebe Island, Central Halmahera, North Maluku - Nur Bambang Priyo Utomo; . Sulistiono; Ridwan Affandi; Thomas Nugroho; Mufti Murhum; Hardono Manan (Institut Pertanian Bogor, 2018)
Gebe Island is one of the islands in Central Halmahera of North Maluku Province. The island has a high potential of fishery resources both for capture and aquaculture fisheries. This activity was carried out from June 2011–September 2015, aimed to improve community’s skill to stock and rear the lobster (Panulirus spp.) in floating net cage at Umera and Umiyal Villages for community empowerment in the Gebe Island. Methods of these activities were training and accompaniment. Smaller size lobsters (3–4 individual per kg) were collected naturally from the sea around the Gebe Island. Based on the observation, lobster farmers community of Umera and Umiyal Villages have been stocking and rearing the lobster. The community can also harvest and sell the lobster collected from the sea reared for 2–4 months in the floating net cage.